MR imaging of degenerative disc disease. Issue 9 (September 2015) - Farshad-Amacker, Nadja A.; Farshad, Mazda; Winklehner, Anna; Andreisek, Gustav
Highlights: This systematic literature review summarizes the current knowledge on MR imaging in degenerative disc disease. Different classification systems for segmental spine degeneration are summarized. It outlines the diagnostic limitations of MR imaging. Abstract: Magnet resonance imaging (MRI) is the most commonly used imaging modality for diagnosis of degenerative disc disease (DDD). Lack of precise observations and documentation of aspects within the complex entity of DDD might partially be the cause of poor correlation of radiographic findings to clinical symptoms. This literature review summarizes the current knowledge on MRI in DDD and outlines the diagnostic limitations. The review further sensitizes the reader toward awareness of potentially untended aspects of DDD and the interaction of DDD and endplate changes. A summary of the available classifications for DDD is provided.